Deep Mycosis (Phycomycosis) - Khan, Inam Ullah; Khan, Miraj Muhammad; Nazeer, Sheikh; Khattak, Khan Nawaz (Journal of Postgraduate Medical Institute, 2011)
We are reporting a case of Deep Mycosis involving the skin and the bone with atypical presentation. This is the first case report of phycomycosis from North Western Frontier Province of Pakistan.